1975
DOI: 10.1071/ph750239
|View full text |Cite
|
Sign up to set email alerts
|

Australian Journal of Physics Astrophysical Supplement

Abstract: A catalogue of 34S radio sources is presented, covering right ascensions O&h 00'" to 17 h OO'" and 19 h 30'" to 06h30'" between declinations _4° and -30°. The regions omitted are within -10° of the galactic plane. The catalogue was compiled from a 'fast' finding survey at 2700 MHz aimed at detecting sources stronger than o· 5 Jy. Subsequent measurements of flux density and position were made on all the sources which were not in the Parkes 40S MHz catalogue, and on some sources in the Parkes 40S MHz catalogue f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…It has been suggested by Bridle and Feldman (1972) that steep-spectrum extended radio sources may be associated with X-ray emission as the result of inverse Compton scattering of the synchrotron electrons from the microwave background. No definite support for this suggestion could be found among the present results.…”
Section: Cluster Luminosity Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested by Bridle and Feldman (1972) that steep-spectrum extended radio sources may be associated with X-ray emission as the result of inverse Compton scattering of the synchrotron electrons from the microwave background. No definite support for this suggestion could be found among the present results.…”
Section: Cluster Luminosity Functionmentioning
confidence: 99%
“…Although there is a diversity of absolute flux density scales at low frequencies, reasonably accurate spectral indices may be obtained by making systematic flux density adjustments. The data used are : 80 MHz, Higgins (1973, 1975); 85 MHz, Mills et al (1958);178 MHz, Goweret al (1967); 1420MHz, Ekers (1969, Murdoch (1976); 2700 MHz, Ekers (1969), Bolton et al (1975), Murdoch (1976, Wall et al (1971); 5000 MHz, Bolton et al (1975), Wall et al (1976). Flux density adjustment factors of 1· 2 and 1· 15 were applied to the 80 and 178 MHz data respectively.…”
Section: Cluster Luminosity Functionmentioning
confidence: 99%
“…These references have been taken from the MC1 list. Three of the sources are included in the Parkes 2700 MHz survey (Bolton et al 1975;Wall et al 1976) and are distinguished simply by the note PKS. Contour maps for some of the sources are given in Figs 1-18, and details of the maps are listed in Table 5.…”
Section: Source Cataloguementioning
confidence: 99%
“…First detected at radio frequencies (Bolton et al 1975), it was observed at X-rays by the Einstein observatory (Zamorani et al 1981) and later studied with ASCA (Cappi et al 1997;Siebert et al 1996), ROSAT (Fiore et al 1998), XMM (Reeves et al 2001) and Swift (Sambruna et al 2007). These observations showed an extremely luminous quasar (L x = 10 47 erg s −1 in the 0.1-2 keV range) with a particularly hard spectrum (Γ = 1 measured by Swift/BAT) and a weak iron K emission line and reflection features.…”
Section: Introductionmentioning
confidence: 99%